Government Legal Policy: Dampak Pembebasan Bersyarat Narapidana selama Pandemi COVID-19 - Aisya Sanghra Devi Nugraha; Eliza Putri Sanggarwati; Sholahuddin Al-Fatih (Universitas Muhammadiyah Malang, 2021)
The government's policy of releasing thousands of public prisoners from various prison institutions in Indonesia is a dilemma. The granting of guarantees of rights to prisoners on the other hand will have various consequences when prisoners re-mingle in the community with social and economic conditions that are not easy in the midst of the current pandemic. Caused by a pandemic that occurred in the world today, namely a disease called Coronavirus Disease (Covid) 19. This disease is caused by the virus Systemic Acute Respiratory Syndrome (SARS) Coronavirus-2 (SARS-COV2). The covid pandemic 19 outbreak in addition to being a breath of fresh air for prisoners in Indonesia, also caused confusion in the community. Because the minister of law and human rights released thousands of prisoners in prison, while the police tried to arrest PSBB violators (Large-scale Social Restrictions) and of course criminalized and put offenders into prison cells. With these conditions, did this pandemic outbreak go down, because previously prisoners had been isolated in prison and were not touched by the outside environment. So the prisoner is actually safe in the cell, and there is no need for parole. Then with the decision to release prisoners during the Covid-19 pandemic it had several impacts on the community, which led to committing crimes. This crime occurred due to the community's economy which declined dramatically, there was no work in the midst of the plague that made the prisoners determined to commit crime. Abstrak Kebijakan pemerintah membebaskan ribuan narapidana umum dari berbagai lembaga permasyarakatan (lapas) di Indonesia menjadi dilema tersendiri. Diberikannya jaminan hak kepada narapidana tersebut di sisi lain akan menimbulkan berbaAgai konsekuensi ketika narapidana kembali membaur di lingkungan masyarakat dengan kondisi sosial dan ekonomi yang tidak mudah di tengah pandemi saat ini. Disebabkan adanya pandemi yang terjadi di dunia saat ini yaitu sebuah penyakit yang dinamai Coronavirus Disease (Covid)-19. Penyakit ini disebabkan oleh virus Systemic Acute Respiratory Syndrome (SARS) Coronavirus-2 (SARS-COV2). Wabah pandemi Covid-19 selain menjadi angin segar bagi para narapidana di Indonesia, juga menjadi kebingungan dalam masyarakat. Karena menteri hukum dan ham membebaskan ribuan narapidana di penjara, sedangkan aparat kepolisian berupaya menangkap pelanggar PSBB (Pembatasan Sosial Berskala Besar) dan tentunya mempidanakan serta memasukkan pelanggar ke dalam sel penjara. Dengan kondisi yang demikian, apakah membuat wabah pandemi ini menjadi turun, karena sebelumnya narapidana sudah di isolasi di dalam penjara dan tidak tersentuh lingkungan luar. Jadi napi sebenarnya sudah aman di dalam sel, dan tidak perlu adanya pembebasan bersyarat. Kemudian dengan adanya keputusan dibebaskannya narapidana di tengah pandemi Covid-19 menimbulkan beberapa dampak bagi masyarakat, yang mengarah untuk melakukan kejahatan. Kejahatan ini terjadi di akibatkan ekonomi masyarakat yang menurun drastis, tidak ada pekerjaan di tengah wabah yang membuat para narapidana nekat melakukan kejahatan.